Penggunaan Bahasa Simbolik-Metafora dalam Pengajian Gus Baha Tafsir QS. Yasin Pada Youtube Al-Muhibbin Channel dan Santri Gayeng - Siti Nur Umdati Putriyani; Dadan Rusmana; Wildan Taufiq (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research is presented with a study of the jalalyn interpretation presented by Gus Baha through the YouTube channel. Massive use of new media is increasingly difficult to control which results in various new problems, namely the competence of a mufassir (whether or not it is appropriate to interpret the Qur'an) as well as problems related to effectiveness in conveying the contents of his verses which are prone to deviations due to technological developments. The method used in this study is qualitative with virtual ethnographic characteristics, namely by collecting various data from the internet, namely YouTube. The interpretation theory used by Gus Baha is that which was initiated by al-Farmawi and Nasharuddin Baidan and then reviewed with semiotics using Charles Pierce's theory. The tahlili method and the fiqh style are the methods used by Gus Baha in interpreting them. The research results in this case show various symbols that explain from one word to another with meanings that become long resulting in an understanding of the science of fiqh. When Gus Baha mentions this verse, it enters the object symbolThis research is expected to add to the body of knowledge for readers as well as if deficiencies are found it can be perfected and corrected in subsequent research.